The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1007/s13592-015-0404-8
|View full text |Cite
|
Sign up to set email alerts
|

Beekeeping practice: effects of Apis mellifera virgin queen management on ovary development

Abstract: -Newly emerged virgin queens are frequently imprisoned in cages either inside or outside of colonies before delivery to a new hive. Ovary integrity and proper functioning is the primary factor in a queen's success as the colony mother. In this work, histological studies on ovaries are used to evaluate the effect of virgin queen imprisonment both out and inside the colony. The results show that the ovarian follicles of virgin queens maintained out of the colony advance only until the beginning of differentiatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 24 publications
(23 reference statements)
0
1
0
Order By: Relevance
“…Queens with undeveloped ovaries have a smaller volume of abdomen and are lighter, thus they are easier to fly (Harano, Sasaki, & Sasaki, 2007), which facilitates mating and fertilization. Berger, Poiani, and Cruz-Landim (2016) reported that the contact of the virgin queen with the workers within the colony is fundamental for complete ovarian development and therefore the queen bank was the most appropriate method to maintain the queens without harming their fertility. The same authors noted that there is a more rapid decline in queen fertility when they are kept in BOD incubators, probably due to the lack of pheromone interaction.…”
Section: Introductionmentioning
confidence: 99%
“…Queens with undeveloped ovaries have a smaller volume of abdomen and are lighter, thus they are easier to fly (Harano, Sasaki, & Sasaki, 2007), which facilitates mating and fertilization. Berger, Poiani, and Cruz-Landim (2016) reported that the contact of the virgin queen with the workers within the colony is fundamental for complete ovarian development and therefore the queen bank was the most appropriate method to maintain the queens without harming their fertility. The same authors noted that there is a more rapid decline in queen fertility when they are kept in BOD incubators, probably due to the lack of pheromone interaction.…”
Section: Introductionmentioning
confidence: 99%